Effectiveness of Large Soil Grain Sizes in Studying Impulse Characteristics of Soil - Muhd Shahirad Reffin; Normiza Mohamad Nor; Nurul Azlina Abdul Rahman; Noradlina Abdullah; Norhasliza Hatta; Mohd Pauzi Yahaya (Energies, 2022)
There have been many published studies analysing the impulse characteristics of soil and various soil properties. Some of these published results are found to be largely different and inconsistent from one study to another. Soil properties may be complex in nature, and its characteristics under high impulse conditions are influenced by many factors, which result in inconsistency in the results. Nevertheless, it has been known that under high impulse conditions, ionisation in the soil would occur due to air discharges in the air voids within the soil, and interfaces between the soil and the ground electrodes. It is also possible that the expansion of the ionisation zone, leading to the occurrence of breakdown in soil, gives better conduction in soil, producing longer streamers and higher magnitudes of current. However, limited study on the impulse breakdown characteristics of soil is found, which was believed to have been due to voltage/current magnitudes that are not high enough to cause the occurrence of soil breakdown. It is important to determine the factors that will cause breakdown to occur in soil when subjected under high impulse conditions since this will give more effective grounding systems when subjected to high impulse conditions. This paper shows that the soil grain size contributes to the most pronounced factor in influencing the soil characteristics under high impulse conditions, in comparison to any other factors. This paper considers thirty-two soil samples containing various percentages of water contents, subjected to high impulse conditions. The soil samples are housed in a hemispherical environment with two different active electrodes, and pre-breakdown and breakdown characteristics of various soils, configurations and percentage of water content are studied.